Validation of a mouse model with Apoe gene knockout - Petr R. Lebedev (Research Results in Pharmacology)
Introduction: The research focuses on the ApoE-/- transgenic mouse model. This model enhances the understanding of the mechanisms underlying disease progression and allows for the testing of new therapeutic strategies.